28.3k views
17 votes
X²+y²-6x+14y-1=0
and please show your work so I can learn

1 Answer

12 votes

Hello there,

I hope you and your family are staying safe and healthy during this winter season.


x^2 + y^2 -6x+14y-1=0

We need to use the Quadratic Formula*


x =(-b+√(b^2)-4ac )/(2a) ,
(-b-√(b^2) -4ac )/(2a)

Thus, given the problem:


a = 1, b=-6, c=y^2+14y-1

So now we just need to plug them in the Quadratic Formula*


x=(6+2√((-6)^2-4(y^2+14y-1)) )/(2) ,
x=(6-√((-6)^2-4(y^2+14y-1)) )/(2)

As you can see, it is a mess right now. Therefore, we need to simplify it


x=(6+2√(10-y^2-14y) )/(2),
x = (6-2√(10-y^2-14y) )/(2)

Now that's get us to the final solution:


x=3+√(10-y^2-14y),
x=3-√(10-y^2-14y)

It is my pleasure to help students like you! If you have additional questions, please let me know.

Take care!

~Garebear

User Bertrand Martel
by
6.2k points